Refining the Role of EGR1 as a Biomarker in MASLD [Letter] - Zeng X (Journal of Inflammation Research)
Xuefan Zeng Chongqing Medical University, Chongqing, People’s Republic of ChinaCorrespondence: Xuefan Zeng, Chongqing Medical University, No.21, Mid University Town Road, Chongqing, 400016, People’s Republic of China, Email zxfcqmu@163.com